1993
DOI: 10.3171/jns.1993.78.2.0192
|View full text |Cite
|
Sign up to set email alerts
|

Transluminal angioplasty for atherosclerotic disease of the vertebral and basilar arteries

Abstract: Transluminal angioplasty for hemodynamically significant stenosis (> 70%) involving the posterior cerebral circulation is now being performed by the authors in selected cases. A total of 42 lesions affecting the vertebral or basilar artery have been successfully treated by percutaneous transluminal angioplasty techniques in 41 patients. The lesions involved the proximal vertebral artery in 34 cases, the distal vertebral artery in five, and the basilar artery in three. Patients were examined clinically at 1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(102 citation statements)
references
References 24 publications
1
101
0
Order By: Relevance
“…44 -49 Complication rates are estimated to be substantial and may stem from vessel rupture, thromboembolic events, or damage to small perforators and subsequent infarction. 45,47,48 It is only because the prognosis of basilar occlusion is so grave that these risks can be both tolerated and ethically justified. Our study documents the sequential use of chemical, followed by mechanical means of recanalization of the basilar artery.…”
Section: Percutaneous Transluminal Cerebral Angioplasty For Strokementioning
confidence: 99%
“…44 -49 Complication rates are estimated to be substantial and may stem from vessel rupture, thromboembolic events, or damage to small perforators and subsequent infarction. 45,47,48 It is only because the prognosis of basilar occlusion is so grave that these risks can be both tolerated and ethically justified. Our study documents the sequential use of chemical, followed by mechanical means of recanalization of the basilar artery.…”
Section: Percutaneous Transluminal Cerebral Angioplasty For Strokementioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] In the present study, TAS for occluded lesions was shown to be technically feasible with a high success rate, similar to treatment of stenotic lesions. Technical success in treating the occluded lesion depends on the freshness of the occluded clots and the occluded segment being short enough for the microguidewire to pass through it; such conditions are frequently encountered in the acute stroke stage.…”
Section: Discussionmentioning
confidence: 84%
“…The procedure-related complication rate in the present study was higher than the reported rates in previous studies performed mainly for stenotic lesions and in the chronic stroke stage. [2][3][4][5][6][7][8][9][10] This may be because TAS for occluded lesions tends to induce distal embolism, intracranial hemorrhage involving hemorrhagic transformation and cerebral hyperperfusion syndrome, and vessel injury or rupture in comparison with the treatment of stenotic lesions. Because distal embolism tends to occur for a lesion crossed by a microguidewire, balloon catheter, or stent and is especially common with occluded lesions, the use of an embolic protection device with proximal flow control may reduce the incidence of this complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with symptomatic or asymptomatic, severe intracranial atherosclerotic stenosis who were at high risk for stroke or death were included (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Intracranial Angioplasty and Stentingmentioning
confidence: 99%